Selective laser melting of lattice structures : a statistical approach to manufacturability and mechanical behavior - Sing, Swee Leong (2019)
This paper investigates the effect of processing parameters on the dimensional accuracy and mechanical properties of cellular lattice structures fabricated by additive manufacturing, also known as 3D printing. The samples are fabricated by selective laser melting (SLM) using novel titanium-tantalum alloy. The titanium-tantalum alloy has the potential to replace commercially pure titanium and Ti6Al4V as biomedical material. In this study, the unit cell used is specially designed to carry out the analysis using regression method and analysis of variance (ANOVA). Due to the effect of the SLM process parameters, the elastic constant of the cellular lattice structures ranged from 1.36 ± 0.11 to 6.82 ± 0.15 GPa using the same unit cell design. The elastic constant range, while showing the versatility of titanium-tantalum as biomedical material, is rather wide despite using the same lattice structure designed. This shows that there is a need to carefully control the processing parameters during the lattice structures fabrication so as to obtain the desired mechanical properties. Based on the statistical analysis, it is found that the dimensional accuracy and mechanical properties such as elastic constant and yield strength of the cellular lattice structures are most sensitive to laser power as compared to other parameters such as laser scanning speed and powder layer thickness.